Serving the Choctaw cause: Robert M. Jones, sovereignty, and pragmatic diplomacy during the American Civil War. Issue 2 (3rd May 2016) - Fortney, Jeffrey L.
ABSTRACT: This article examines how the Choctaw Nation aligned with the Confederacy while remaining a united, autonomous nation during the American Civil War. Rather than being hapless or coerced, Choctaw leaders demonstrated clear comprehension, agency, and pragmatism in their wartime efforts. In particular, Choctaw political leaders like Robert M. Jones reveal the Choctaws' larger efforts to protect their national sovereignty and defend their homelands. Moreover, the actions of Jones and other Choctaws during the war highlight the critical role that sovereign tribal nations played in the American Civil War.